Variation in electrical conductivity of conductive polymer composites under shock wave. (December 2015) - Chen, Jian-kang; Lei, Jin-tao; Zhang, Ming-hua; Bai, Shu-lin
Highlights: Under loading wave, the conductivity of conductive polymer composites increases. Under unloading wave, the conductivity of conductive polymer composites decreases. The decrease of conductivity under unloading wave is induced by micro-damage evolution. Abstract: The piezoresistive effect is an important property of conductive polymer composites (CPCs), but the conductive behavior of the composite under shock wave of high pressure and high strain rate, including incident wave and reflected wave, needs to be further studied. To characterize such a system, we study the variation in electrical conductivity of a conductive polymer composite under shock waves, including loading wave and unloading wave, in this paper. The polymer matrix is polyamide-6 with carbon nanotubes and stainless steel fibers are the fillers. The data indicate that the resistivity decreases under the loading shock wave, but sharply increases due to the unloading shock wave. Scanning electron microscopy (SEM) reveals that this resistivity increase is due to damage by the unloading wave and subsequent failure of many micro-conductive channels in the material.